« But from the over-curious and vain / Distempers of an artificial brain »: La satire de la curiosité vaine chez Samuel Butler (1612-1680) - Nicolas Correard (Etudes Epistémè)
Frequent among Renaissance humanists, the criticism of vain curiosity became popular again with the rise of new science throughout the XVIIth century, as can be seen in the works of Restoration satirical writers, who targeted the Royal Society from when it came into being. Samuel Butler is a case in point: although his work is little known, vain curiosity is a recurrent theme of his works, whatever the genre, be it in his mock-epic, in his philosophical essays, in his character book or in his philosophical poetry. An overall view shows how the old stereotypes, still applicable to philosophers, encyclopaedic pedants or collectors, are transferred to the figure of the experimental philosopher (‘Virtuoso’). Besides the moral or political grievances, Butler’s scepticism was first and foremost aimed at the methods and epistemological ambition of the ‘novatores’, and being well-informed, Butler profusely applied satiric parody to early-modern science.